Benefits of Low-Dose Aspirin During Pregnancy: A Systematic Review - Cut Mourisa (Universitas Muhammadiyah Sumatera Utara, 2023)
Abstract: Low-dose aspirin therapy (LDA) is reported to give good results on the outcome of pregnancy. This systematic review study aims to find out in what cases the role of LDA can be given, the amount of dose and duration of administration and the final results of various studies that have been conducted. Researchers used a systematic literature study with the help of Publish or Perish, Mendeley and Microsoft Excel applications in a literature search from Google Scholar with the keyword low dose aspirin related to pregnancy. Of the 200 articles taken, after conducting a systematic assessment, 21 articles were included in the inclusion criteria that discussed 4 topics, namely pre-eclampsia, current pregnancy loss, healthy pregnancy and inflammatory cases in pregnancy. From the results of the review, it can be concluded that low-dose aspirin can be used and is beneficial in preventing and treating some complications in pregnancy. Its administration can be given before conception until gestational age reaches 36 weeks with a dose range of 50 mg to 150 mg per day.